1982
DOI: 10.1203/00006450-198211000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of the Lung in Prolonged Bronchopulmonary Dysplasia

Abstract: Summary Speculation MATERIALS AND METHODSSevere neonatal lung injury, with persistent oxygen dependency throughout infancy might result in inhibition or marked slowing of lung growth. Because development of conducting airways is completed early during intrauterine life and because most alveolar development takes place postnatally, one might expect disturbances in alveolar growth to overshadow residual airway injury in survivors of bronchopulmonary dysplasia.Morphometric analysis of the lungs and heart of a mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
0
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(45 citation statements)
references
References 14 publications
2
42
0
1
Order By: Relevance
“…We suggest this because: I ) very low birth weight premature infants may require elevated F102 therapy for periods of months; and, 2) this hyperoxic treatment is occurring at a time when the fetal lung should normally be entering its most rapid phase of lung development and surface-area expansion (with the normal formation of an estimated 40 x lo6 alveoli between 26 wk gestation and term) (45,46). In recent years, several morphometric studies of the lungs of human infants who died with chronic lung disease (bronchopulmonary dysplasia) have clearly illustrated much-enlarged terminal air spaces, markedly reduced total number of alveoli, and proportionately reduced lung internal surface area (47)(48)(49). These changes indeed appear quite similar to the findings of morphometric studies in the hyperoxiaexposed newborn animal.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…We suggest this because: I ) very low birth weight premature infants may require elevated F102 therapy for periods of months; and, 2) this hyperoxic treatment is occurring at a time when the fetal lung should normally be entering its most rapid phase of lung development and surface-area expansion (with the normal formation of an estimated 40 x lo6 alveoli between 26 wk gestation and term) (45,46). In recent years, several morphometric studies of the lungs of human infants who died with chronic lung disease (bronchopulmonary dysplasia) have clearly illustrated much-enlarged terminal air spaces, markedly reduced total number of alveoli, and proportionately reduced lung internal surface area (47)(48)(49). These changes indeed appear quite similar to the findings of morphometric studies in the hyperoxiaexposed newborn animal.…”
Section: Resultssupporting
confidence: 75%
“…These changes indeed appear quite similar to the findings of morphometric studies in the hyperoxiaexposed newborn animal. The recent pathologic study by Margraf et al (47) also demonstrates the reduced elastin fiber deposition and altered (frayed) appearance of the elastin fibers in the lungs from premature infants who died from chronic lung disease after long-term O2 treatment. The degree of inhibition of normal lung development in these 02-requiring infants with bronchopulmonary dysplasia is dramatic, with a total lung alveoli complement of only 20 to 40 x lo6 versus 60 to 200 x lo6 for agematched control infants and internal respiratory exchange surface areas totaling (1.0 m2 versus the normal values of 2 to 6 m2 (49).…”
Section: Resultsmentioning
confidence: 99%
“…Several recent reports, including that by Sobonya, et a/. (43) would seem to support the contention (42-45) that inhibited alveolarization and reduced surface area for respiratory exchange can be a serious consequence of prolonged respiratory support for BPD.…”
Section: Discussionmentioning
confidence: 78%
“…Dexamethasone treatment resulted in fewer alveoli and a smaller gas-exchange surface area, similar to that seen in premature infants with BPD (11)(12)(13). In a subsequent study, Massaro and Massaro (14) demonstrated that the inhibition of alveolarization produced by dexamethasone treatment of newborn rats could be attenuated by the administration of retinoic acid.…”
mentioning
confidence: 84%